Development of Application Based on Augmented Reality as A Learning of History and Culture in Architecture Case Study Pathok Negoro Mosques Yogyakarta - Hendro Trieddiantoro Putro; Endang Setyowati (Journal of Artificial Intelligence in Architecture, 2022)
Pathok Negoro Mosques is an architectural masterpiece. These mosques are part of history in forming Yogyakarta. The existence of the Sultan’s Ngayogyakarta Palace is inseparable from the Pathok Negoro Mosques building. These mosques also have a function as a defensive system of the Islamic kingdom in Yogyakarta. Arguably, the current generation is getting deprived of the intellectual heritage of culture and history. The history and culture of the Pathok Negoro Mosques will be the content of this research. This research aims to develop an interactive application for learning the history and culture of architecture based on augmented reality. Augmented reality applications developed using unity. This research is proposed to be carried out in 2 stages. The first stage is related to the collection of the historical and cultural context of the mosque. The second stage is the development of an AR application for Android mobile devices. The reference data was made into the AR application with several methods, such as plane detection and image tracking. The research managed to develop a mobile augmented reality application in Unity3D 2018.3.14f1 for android devices that consists of the narrative recorded voice of brief history and culture the Pathok Negoro Mosques. The app also shows a well-ordered animation of building structure such as roof, roof insulation, roof structure and column of Pathok Negoro Mosques. Moreover, the research showed a clear step and issue of making an augmented reality app as learning of history and culture of Pathok Negoro Mosques